2000
DOI: 10.1111/j.1574-695x.2000.tb01520.x
|View full text |Cite
|
Sign up to set email alerts
|

Super-infection byBacillus thuringiensisH34 or 3a3b can lead to death in mice infected with the influenza A virus

Abstract: Bacterial super-infections are the main cause of complication and mortality after influenza virus (IAV) infection. Since Bacillus thuringiensis (Bt) is considered non-pathogenic for humans and is widely sprayed in urban areas, the aim of this work was to evaluate the potential pathogenicity of a combined infection Bt-IAV in a mouse model of pneumonia. Bacteria used for super-infections were Bt serotype H34 isolated from human infection and the insecticidal strain 3a3b obtained from a commercial source. Virus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In addition, two other pathogenic isolates, B. cereus Zebra Killer (ZK) and B. thuringiensis 97-27 (subsp. konkukian (serotype H34)) (Hernandez et al, 1998(Hernandez et al, , 1999(Hernandez et al, , 2000 were shown, together with B. cereus G9241, to be closely related to B. anthracis based on phylogenetic analysis using AFLP and MLST (Hill et al, 2004). The proteome of all three isolates show a higher similarity to that of B. anthracis than to that of the non-pathogenic B. cereus ATCC 14579 (Rasko et al, 2005 and references therein).…”
Section: Safety Considerationsmentioning
confidence: 99%
“…In addition, two other pathogenic isolates, B. cereus Zebra Killer (ZK) and B. thuringiensis 97-27 (subsp. konkukian (serotype H34)) (Hernandez et al, 1998(Hernandez et al, , 1999(Hernandez et al, , 2000 were shown, together with B. cereus G9241, to be closely related to B. anthracis based on phylogenetic analysis using AFLP and MLST (Hill et al, 2004). The proteome of all three isolates show a higher similarity to that of B. anthracis than to that of the non-pathogenic B. cereus ATCC 14579 (Rasko et al, 2005 and references therein).…”
Section: Safety Considerationsmentioning
confidence: 99%
“…Main cause of complications and mortality following an avian influenza virus attack, are the secondary bacterial infections. Combined infection with influenza A virus from human infection (4% of the viral lethal dose 50%) and Bacillus thuringiensis (10 7 spores) from a commercial source leading to 100% mortality in mice indicates that non-pathogenic Bacillus species will pose a high risk during bird flu outbreak 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The opportunistic properties of B. thuringiensis and B. cereus have been investigated using nasal instillation in mice (243, 244) and intraocular infection in mice and rabbits (245). In all the cases, the results highlight the importance of the PlcR regulon in the pathogenic properties of these bacteria.…”
Section: Modelling Host Interactions Animal Models For Anthraxmentioning
confidence: 99%